2013
DOI: 10.1021/ja410663g
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Phase Synthesis of Au–Ag Core–Shell Nanocrystals with Tunable Shapes and Their Optical and Catalytic Properties

Abstract: In this study, rhombic dodecahedral gold nanocrystals were used as cores for the generation of Au-Ag core-shell nanocrystals with cubic, truncated cubic, cuboctahedral, truncated octahedral, and octahedral structures. Gold nanocrystals were added to an aqueous mixture of cetyltrimethylammonium chloride (CTAC) surfactant, AgNO3, ascorbic acid, and NaOH to form the core-shell nanocrystals. The nanocrystals are highly uniform in size and shape, and can readily self-assemble into ordered packing structures on subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 40 publications
3
138
0
Order By: Relevance
“…[67][68][69] The current works shows that Ag grown on an Au seed crystal can impact particle structure, especially for shell thicknesses of size comparable or smaller than the core. However, other effects of a seed crystal or core on particle stability need to be considered.…”
Section: -11 Munusamymentioning
confidence: 86%
“…[67][68][69] The current works shows that Ag grown on an Au seed crystal can impact particle structure, especially for shell thicknesses of size comparable or smaller than the core. However, other effects of a seed crystal or core on particle stability need to be considered.…”
Section: -11 Munusamymentioning
confidence: 86%
“…The catalytic properties can be tuned by tuning the size and shape of the nanoparticles. 21 Recently, Xia et al 22 have reported the comparative catalytic activity of the Au nanoparticles, nanoboxes, and nanocages by reduction of nitrophenols. Again, the catalytic property can be tuned with changing the nanoparticle composition from single component to bimetallic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the different morphologies, the core−shell type nanoparticles are most interesting as the core diameter and the shell thickness might play important role on the catalytic activity. Recently, Tsao et al 21 have demonstrated the shape dependent catalytic activity of the Au−Ag core−shell nanocrystals. Thus, the catalytic and other physiochemical activities of the core−shell materials can be tuned by changing the size of the core in core−shell structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They found that Au/Ag core-shell octahedra were more catalytically active than cubes toward the reduction of 2-amino-5-nitrophenol at 30 8C. [150] Oxygen reduction reaction (ORR)…”
Section: Dehydrogenation Of Abmentioning
confidence: 99%